Weight optimization in Enhanced Multivariance Product Representation (EMPR) method - (:unkn) unknown (My University, 2010)
This paper focuses on the weight function optimization in Enhanced Multivariance Product Representation (EMPR) via constancy maximization. This is done by tracing the same philosophy as HDMR weight function optimization. © 2010 American Institute of Physics.
Keywords: Enhanced Multivariance Product Representation; High Dimensional Model Representation; Multivariate Functions; Optimization; Support Functions; Weight Functions